Coincidence Fixed-Point Theorems for p-Hybrid Contraction Mappings in Gb-Metric Space with Application - Lucas Wangwe (Abstract and Applied Analysis)
By combining the notions of G-metric space and b-metric space, in this paper, we present coincidence fixed-point theorems for p-hybrid mappings in Gb-metric spaces. An example is given to demonstrate the novelty of our main results. Henceforth, the illustrative applications are given by using nonlinear fractional differential equations.